1H NMR Chemical Shifts of Adsorbed Molecules on the Carbon Surface - V.V. Turov; R. Leboda (Adsorption Science & Technology)
The chemical shifts of water and organic molecules adsorbed on to different types of carbon surfaces (exfoliated graphite, graphite oxide, intercalated graphite, graphitized and non-graphitized activated carbons, carbon black, carbosils) were studied by 1 H NMR spectroscopy. Values of the chemical shift were found to differ in accordance with the structure of the active sites. This is caused by an anisotropic effect associated with condensed aromatic systems. The maximum values of such changes in the chemical shift were observed with slitlike pores formed by graphite clusters in partly graphitized activated carbons. Some such clusters were also identified in carbon black and carbosils. For water, it was found that the chemical shifts also depended on the number of water molecules taking part in the formation of hydrogen-bonded associates.